Sustainable Development Challenges: Ethical Values of Locality, Environment and Technology on Indigenous Resilience in Pahang Malaysia: - - Syamsiyah, Nur Rahmawati; Rosali, Mohammad Afiq (Universitas Muhammadiyah Surakarta, 2025)
To know more deeply the traditional knowledge and practices of the indigenous people, such as Malaysia’s Orang Asli, is vital for environmental conservation and sustainable development. However, challenges like displacement, cultural erosion, and exclusion from decision-making, worsened by climate change and economic growth-focused policies—threaten their resilience. This paper examines these issues and highlights barriers such as poor legal protections, environmental degradation, and cultural marginalization. The method used is a literature study and field observation in the indigenous people’s village of Pahang, Malaysia. The results of the study, despite these obstacles, the Orang Asli Pahang display resilience through their heritage and selective integration of modern technologies. The study calls for rights-based, participatory approaches to create inclusive policies that protect cultural heritage and leverage indigenous wisdom for sustainable development.